(untitled) (Communications in Computational Physics, 2018)
The linear hyperbolic equation is of great interest in many branches of physics and industry. In this paper, we use the weak Galerkin method to solve the linear hyperbolic equation. Since the weak Galerkin finite element space consists of discontinuous polynomials, the discontinuous feature of the equation can be maintained. The optimal error estimates are proved. Some numerical experiments are provided to verify the efficiency of the method.